Lethal and sublethal effects of the natural and healthy spinosad-based formulation Tracer™ on tadpoles of two neotropical species - Bahl, María Florencia (2020)
This paper presents the first acute toxicity data of the natural insecticide spinosad in amphibians. The sensitivity of two neotropical sympatric anuran species, Boana pulchella and Rhinella arenarum, to spinosad-based formulation Tracer™ was evaluated. Lethal effects are reported in tadpoles of B. pulchella stage 25 between 2.81 and 35.44 mg spinosad/L, while for the same concentration range no lethal effects were detected in tadpoles of R. arenarum of the same stage. In addition, Tracer™ produced sublethal effects at the individual level on the swimming activity, morphology (growth and presence of abnormalities), and development of B. pulchella from 2.81 to 5.78 mg spinosad/L, while in R. arenarum effects were only detected in the swimming activity and growth from 2.78 and 6.22 mg/L, respectively. At the biochemical level, Tracer™ produced inhibition of different enzymatic activities, among them, catalase activity at 2.81 mg spinosad/L, glutathione S- transferase activity from 2.81 to 2.98 mg spinosad/L, and acetylcholinesterase activity at 2.81 mg spinosad/L. These findings allow us to conclude that B. pulchella is more sensitive than R. arenarum to spinosad-based formulation Tracer™. The effects demonstrated here are not consistent with those expected since spinosad is supposed to be an environmental healthy alternative. This paper provides useful and necessary information to implement regulations on the use of new compounds entering the market and its associated risks.